The survey of factors related to self-efficacy based on Orem’s theory in patients with coronary artery bypass surgery in Tehran in 2014 - Salimian, Shahnaz; Esmaieli, Roghayeh; Dabirian, Azam; Mansoorin, Samaneh; Zohari Anboohi, Sima (Advances in Nursing & Midwifery, 2016)
Background & Aim: Utilization of nursing theories for finding the factors associated with self-efficacy in the patients undergoing coronary artery bypass surgery is very important. This study was conducted to determine the factors associated with self-efficacy based on Orem's theory in these patients after coronary bypass surgery. Materials and Methods: This was a descriptive-correlative study. 150 patients undergoing coronary artery bypass surgery were selected with convinince sampling. The data was collected by the demographic questionnaire and the self-efficacy questionnaire. The self-efficacy questionnaire was made based on Orem’s theory of self care. Instroments validity and relability was determined by content validity and Cronbach Alpha(0.095). Data were analyzed using SPSS software ver19. Findings: Results of this research showed that self-efficacy in patients after coronary artery bypass surgery was low(2%), medium(49%) and high(49%). Self-efficacy was significantly correlated with some basic conditioning factors based on Orem’s theory (marital status, employment, level of education, age, income , health insurance and education about surgery). The highest level of self-efficacy were in regard of medication use, regular physician consultation, and low fat and low salt diet consumption at home. Conclusion: Patients after coronary artery bypass surgery were more confident in regard to medication use, regular physician consultation than exercise and stop smoking. This may indicate that Patients have less attention to non-pharmacological aspects (healthy lifestyle and long-term adherence) and selfcare behaviors after coronary artery bypass surgery. It seems that nurses and physicians should emphasize on the effects of non–medical cares more clearly and enhance motivation based on selfefficacy of the patients. Key words: self-efficacy, coronary artery bypass surgery, Orem’s Self Care Model